2017
DOI: 10.1177/1078155217745144
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab for the management of immune mediated adverse events secondary to PD-1 blockade

Abstract: Background Immune checkpoint inhibitors are poised to revolutionize the management of a growing number of malignancies. Unfortunately, the management of steroid-refractory immune mediated adverse events is based on a paucity of randomized data and limited to single center experiences. Our initial experience with the IL-6 receptor antagonist tocilizumab showed clinical improvement in a wide variety of irAEs. As a result, we adopted the use of tocilizumab for the management of steroid refractory irAEs. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
178
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(183 citation statements)
references
References 28 publications
3
178
0
2
Order By: Relevance
“…For instance, a retrospective, single-center series, in which tocilizumab was used as second-line therapy for high-grade irAEs, reported the use of tocilizumab in 34 of 87 patients who were treated with nivolumab for multiple solid tumor types. 32 The most common irAEs treated with tocilizumab were pneumonitis and serum sickness/systemic inflammatory response syndrome, and clinical improvement was observed in 27 of 34 patients. IL-6 expression has been shown to promote tumor growth and metastasis; therefore, IL-6 blockade may offer the potential for the effective treatment of refractory irAEs and maintenance of immunotherapy efficacy.…”
Section: Checkpoint Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a retrospective, single-center series, in which tocilizumab was used as second-line therapy for high-grade irAEs, reported the use of tocilizumab in 34 of 87 patients who were treated with nivolumab for multiple solid tumor types. 32 The most common irAEs treated with tocilizumab were pneumonitis and serum sickness/systemic inflammatory response syndrome, and clinical improvement was observed in 27 of 34 patients. IL-6 expression has been shown to promote tumor growth and metastasis; therefore, IL-6 blockade may offer the potential for the effective treatment of refractory irAEs and maintenance of immunotherapy efficacy.…”
Section: Checkpoint Inhibitorsmentioning
confidence: 99%
“…Some authors have proposed a strategy of the standard use of IL‐6 receptor blockade with tocilizumab in refractory irAEs. For instance, a retrospective, single‐center series, in which tocilizumab was used as second‐line therapy for high‐grade irAEs, reported the use of tocilizumab in 34 of 87 patients who were treated with nivolumab for multiple solid tumor types . The most common irAEs treated with tocilizumab were pneumonitis and serum sickness/systemic inflammatory response syndrome, and clinical improvement was observed in 27 of 34 patients.…”
Section: Checkpoint Inhibitorsmentioning
confidence: 99%
“…The latest treatment frontier against COVID-19 seems to be represented by a recombinant humanized monoclonal antibody, named tocilizumab, which binds the human IL-6 receptor, inhibiting its signal transduction [20]. Tocilizumab is currently used for rheumatoid arthritis, but its efficacy has been demonstrated also against ICI-induced irAEs, starting from the rationale of an ICI-induced systemic inflammatory response syndrome similar to CRS [21]. Moreover, along with the improvement in symptoms related to systemic inflammatory response syndrome, some authors reported a clinical improvement in other irAEs with tocilizumab used in cancer patients with immune-related toxicity from anti-PD-1 agents [21,22].…”
Section: Therapeutic Implications: Tocilizumab and The Risk Of Hasty Comentioning
confidence: 99%
“…While the rational for inflammation control or immune effector modification is supported by both preclinical mechanistic data and clinical correlations, it has not been explored clinically as aggressively as immune stimulatory therapies. The use of tocilizumab (anti-IL-6) to control immune mediated adverse events of immune checkpoint inhibitors, appears to be clinically safe and not inhibit anti-tumor immune function [48]. This supports the concept that inflammatory effector cytokines such as IL-6 are not essential in antigen specific tumor immunity.…”
Section: Tumor Associated Inflammationmentioning
confidence: 79%